The MOAN (Musculo-Osteo-Arthro-Neuropathic) syndrome - Sanjay Kalra; Vijay Kumar; Nitin Kapoor (Journal of the Pakistan Medical Association, 2022)
We share the concept of a multisystemic syndrome which affects the muscle, bone, joints and nerves, in varying manners. The MOAN (musculo-osteo-arthro-neuropathic) syndrome highlights the close relationship between these four organ-systems, and their contribution to each other’s health and disease. The mnemonic MOAN also underscores the discomfort and pain associated with the condition and encourages health professionals to address these patients in a holistic manner, rather than just addressing one of the components. Keywords: Arthritis, Diabetes, Type 2 diabetes, Endocrinology, Geriatrics, Neuropathy, Osteoarthritis, Osteoporosis, Peripheral neuropathy, Sacropenia.